Land Use Change and Coastal Ecosystem Pressure: A CA–Markov Simulation of Mangrove Dynamics in Brandan Barat, North Sumatra, Indonesia - Selyana Nabila; Elysa Wulandari; Joni (Postgraduate, University of Mataram, 2026)
This study analyzes land-use change dynamics and coastal ecosystem pressure in Brandan Barat Subdistrict, Langkat Regency, North Sumatra, using multitemporal satellite imagery and the CA–Markov spatial simulation model. The novelty of this study lies in the integration of land-use change analysis, ecosystem pressure assessment, and predictive spatial modeling using Landsat imagery (30 m resolution) over a 20-year period (2004–2024), validated with Kappa accuracy, to support ecosystem-based coastal spatial planning. The methods used include multitemporal satellite imagery analysis and spatial analysis to identify the dynamics and trends of land-use change, which are integrated with the CA–Markov model to develop spatial planning scenarios based on predictive modeling. The results show a decrease in mangrove area from 2,282.49 ha in 2004 to 1,292.67 ha in 2014, followed by a slight increase to 1,367.01 ha in 2024, with a total reduction of 915.48 ha during the 2004–2024 period. In contrast, plantation areas increased from 2,792.88 ha in 2004 to 3,748.86 ha in 2014 and 3,775.50 ha in 2024. These conditions increase pressure on protected zones and potentially reduce environmental carrying capacity. Simulation results indicate that controlling land conversion, rehabilitating mangroves, and strengthening spatial planning based on environmental carrying capacity are effective in reducing ecosystem degradation. These findings emphasize the importance of adaptive and ecosystem-based coastal planning that can be replicated in other tropical coastal areas.